PDF Study the Effect of Nano Aluminum Oxide Coating on PMMA as Thermal Insulator: Dawood Obied Altiafy *, Hussien Ali Jawad, Noor Taha Ismaeel - abed, L.dawood; Jawad, Hussien (Iraqi Journal of Laser, 2022)
Abstract: In the present work, the heat transfer of Nano Aluminum Oxide -NAO- has been studied practically to define the appropriate insulation conditions.  This study focuses on finding of the amount of heat transfer through a glass substrate that is coated with nanoalumina doped on PMMA matrix. The optical and thermal properties were systematically investigated. The density of heat flow rate, was calculated in the range values (240-260) W/m2 while the optimum values confine between (250-260) W/m2 at temp. (25-35)Co. The results showed that the thermal insulation of the sample was significantly enhanced at temp. (30-50)Co. The simulated net heat transfer through window decreased linearly with increase of both of coating thickness concentration. Furthermore, the overall transmittance in the visible region and reflectance in infrared and ultraviolent regions decrease with increasing of weight content of the coated film.